AAV-mediated gene therapies for glaucoma and uveitis: are we there yet? - Brenda Castro; Jason C. Steel; Christopher J. Layton (Expert Reviews in Molecular Medicine)
Glaucoma and uveitis are non-vascular ocular diseases which are among the leading causes of blindness and visual loss. These conditions have distinct characteristics and mechanisms but share a multifactorial and complex nature, making their management challenging and burdensome for patients and clinicians. Furthermore, the lack of symptoms in the early stages of glaucoma and the diverse aetiology of uveitis hinder timely and accurate diagnoses, which are a cause of poor visual outcomes under both conditions. Although current treatment is effective in most cases, it is often associated with low patient adherence and adverse events, which directly impact the overall therapeutic success. Therefore, long-lasting alternatives with improved safety and efficacy are needed. Gene therapy, particularly utilising adeno-associated virus (AAV) vectors, has emerged as a promising approach to address unmet needs in these diseases. Engineered capsids with enhanced tropism and lower immunogenicity have been proposed, along with constructs designed for targeted and controlled expression. Additionally, several pathways implicated in the pathogenesis of these conditions have been targeted with single or multigene expression cassettes, gene editing and silencing approaches. This review discusses strategies employed in AAV-based gene therapies for glaucoma and non-infectious uveitis and provides an overview of current progress and future directions.